Radioactive : the women of Three Mile Island [videorecording (DVD)] - Hart, Martjin; Grange, Roger; Caniglia, Valentina; Hammerstein, Dash; Fonda, Jane, 1937-; Drazba, Beth; Kinney, Paula; Braasch, Linda (First Run Features : Kino Lorber, 2023)
In this thrilling feminist documentary, indomitable women fight back against the nuclear industry to expose one of the worst cover-ups in U.S. history. RADIOACTIVE: The Women of Three Mile Island is an award-winning film about the 1979 Three Mile Island meltdown the worst commercial nuclear accident in U.S. history and its aftermath. It uncovers the never-before-told stories of four intrepid homemakers who take their local community's case against the plant operator to the Supreme Court and a young female journalist who's caught in the radioactive crossfire.